Immunization, new viruses, and new vaccines - Naveen Thacker; Vipin M Vashishtha; Sayali Lawate (Elsevier, 2024)
A global outbreak of Coronavirus Disease 2019 (COVID-19) which is caused by a new virus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has just occurred. An instance of an infectious virus that has been transmitted to humans and had a substantial effect on worldwide health and the economy is SARS-CoV-2. In the human population, besides SARS-CoV-2, numerous additional viruses have lately emerged or re-emerged. To accurately predict the hazards of emerging and re-emerging viral infections, close cooperation between the public health system and the scientific community is essential. Some of the reasons that may be related to the emergence and re-emergence of novel viruses include urbanization, alterations in the natural environment, globalization, and insufficient public health infrastructure.Vaccines will aid in efficiently controlling the intense outbreaks caused by these emerging viruses. Nevertheless, the creation of novel vaccines encounters various obstacles, including tight deadlines for development and the ongoing evolution of viral variants. Notwithstanding, the difficulties encountered in vaccine development, recent progress in the vaccine development process has yielded a significant breakthrough in combating disease outbreaks. Recent advancements in immunology, genetics, and biotechnology have enabled the creation of several vaccines, including those for dengue, RSV, chikungunya, malaria, and most notably, COVID-19. These novel vaccinations protect a broad spectrum of viruses and other pathogenic microorganisms, including those that are challenging to control or have just emerged.